Case Report: Focal xanthogranulomatous pyelonephritis in children: diagnostic pitfalls and the role of conservative management - Aziza, Bochra; Sghairoun, Nada; Ghaddab, Nader Bennour; Houas, Yasmine; Jlidi, Said (Frontiers in Nephrology, 2025)
BackgroundFocal xanthogranulomatous pyelonephritis (XGP) is a rare chronic renal inflammatory disorder in children that often mimics renal neoplasms, complicating diagnosis and management.MethodsWe describe two pediatric cases of focal XGP managed at our institution and provide a descriptive review of the literature (1975–2024), analyzing clinical presentation, imaging features, management strategies, and outcomes of this disease.ResultsCase 1: A 2-year-old boy presented with a febrile right flank mass and systemic inflammation. CT Scan revealed an 80 mm multilocular renal mass. Surgical drainage and biopsy confirmed focal XGP, and targeted antibiotics led to complete resolution with preserved renal function at two-year follow-up. Case 2: A 10-year-old girl presented with a 40 mm left renal mass and systemic inflammatory signs. CT-guided aspiration and histopathology confirmed focal XGP. She was managed conservatively with intravenous and oral antibiotics, achieving complete resolution and normal renal function at seven-year follow-up. Literature review of 34 pediatric XGP cases (median age 11.1 years) showed that 53% were focal lesions. Conservative management with antibiotics, with or without drainage, succeeded in 64% of cases, and overall outcomes were favorable, with stable renal function and no reported mortality.ConclusionThis combined case series and descriptive literature review highlights that conservative, kidney-sparing management is a feasible and effective approach in selected pediatric focal XGP cases. Multicenter collaborations are needed to define standardized diagnostic and therapeutic protocols.